Hipertensi Pada Kehamilan Dan Kejadian BBLR di RSUD Kota Tasikmalaya - Lia Herliana (Sehat MasadaJurnal, 2019)
LBW babies often make it risky not only because of neonatal complications experienced (eg hyperbilirubinemia and respiratory distress syndrome) but also by other risk factors (eg congenital anomalies associated with LBW). LBW requires proper management by a nurse because if it does not get adequate care, LBW will have an impact on the respiratory system, vision system, reflexes, motor movements and even long-term effects of learning difficulties and behavior (neurobehavior). This research is motivated by the high incidence of LBW in Tasikmalaya City Hospital in each year so that it is necessary to trace the causes of LBW events experienced. The aim of the study was to determine the relationship between hypertension in pregnancy and the incidence of LBW in Dr. Soekardjo, Tasikmalaya City. The research hypothesis has a relationship between hypertension in pregnancy and the incidence of LBW. The benefits of research provide a basis for evidence-based practice to nursing practitioners, that there is a relationship between hypertension in pregnancy and the incidence of LBW. Quantitative research method with approach cross sectional. Processing data using univariate and bivariate analysis. The results of the study there was no significant relationship between hypertension in pregnancy with the incidence of LBW in Tasikmalaya City Hospital with p value> 0.05. Suggestions should nurses further improve health education in the community so that people better understand the risks of LBW.